Interactions between building information modelling and off-site manufacturing for productivity improvement - Ghasemi Poor Sabet, Pejman; Chong, Heap-Yih (John) (EMERALD GROUP PUBLISHING LTD, 2019)
© 2019. Emerald Publishing Limited.